Case Report: Two cases of hereditary angioedema in a Chinese family - Yuanli Guo; Manli Qi; Jinluan Ding (Frontiers in Allergy)
BackgroundHereditary angioedema (HAE) is a life-threatening condition characterized by repeated asymmetric cutaneous and mucosal edema. It is a rare autosomal dominant genetic disease with a mortality rate of 8.6%. Family survey of HAE in China is seldom reported since it is still under recognized.Case reportWe reported two cases of HAE and a family survey conducted in Hebei Province, China. The proband was a woman who had edema for over 7 years. She was diagnosed with type I HAE in her 50s after a life-threatening asphyxia attack. Her elder brother was initially diagnosed with mild symptoms.ConclusionTwo diagnosed and three suspected patients were identified in our family survey. Family surveys are important method for identifying asymptomatic patients and preventing attacks. It is valuable for rescuing people from sudden death, particularly from asphyxia.